Acoustic properties of polyurethane composite with both millimeter-scale closed cavity and nanometer-scale semi closed cavity. (June 2022) - Yu, Tianmiao; Jiang, Fengchun; Chen, Yongyao; Cao, Mengxin; Wang, Chunhe; Qin, Ruonan; Guo, Chunhuan
Abstract: Noise pollution has become a major public hazard in modern society. Therefore, it is very important to develop materials with good sound insulation and sound absorption properties, and cavity structure materials have been widely used in this field. Among the many cavity structure materials, metallic hollow spheres (MHS) is a kind of closed cavity structure with millimeter-scale, and multi-walled carbon nanotubes (MWCNTs) is a kind of semi closed tubular structure with nanometer-scale. Therefore, in this study, multi-walled carbon nanotubes (MWCNTs) were coated on the surface of 316L hollow spheres (316L HS), and then the modified MHS were added into polyurethane (PU) matrix to form the PU/MWCNTs/316L HS composite. Through acoustic test, it can be found that the acoustic performance of PU/MWCNTs/316L HS has been greatly improved compared with PU/316L HS. It is demonstrated that the synergistic effects of metallic hollow spheres and MWCNTs could significantly improve the acoustic performance of composite. Graphical Abstract: ga1